Interaktive Radiosendungen und die Rolle neuer Informationsmittler in der Republik Benin (Global Media Journal - German Edition, 2024)
This study investigates interactive forms of public communication in the Republic of Benin (West Africa) with a specific focus on the emergence of new media actors. Benin’s media landscape features a variety of media formats, which are constantly incorporating interactive elements. These developments result in novel roles for both media producers and audiences. This analysis examines communication processes in radio call-in shows on social issues in the Republic of Benin that utilize participatory media formats. The primary figures of interest in these shows are frequent callers who participate in grievance-oriented programmes. Known as ‘grogneurs’, these individuals have now established themselves as respected information brokers within the country. What factors contribute to their prominence, and what are the implications of their success for information practices in the region? This study is using ethnographic methods and examines the motives, skills, and strategies that underpin grogneurs’ information acquisition, networking, and legal protection. It also examines grogneurs’ relationships with journalists, authorities, and broader radio audiences. The article argues that, despite potential role overlap between journalists and grogneurs, both groups endeavour to maintain clear distinctions in their roles to safeguard their reputation and foster interactive media formats.
Keywords: Radio; Westafrika; Benin; frequent callers; call-in shows; information brokerage